2015
DOI: 10.1371/journal.pone.0131124
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y Stimulates Proliferation and Migration of Vascular Smooth Muscle Cells from Pregnancy Hypertensive Rats via Y1 and Y5 Receptors

Abstract: The increased proliferation and migration of vascular smooth muscle cells (VSMCs) play important roles in pathophysiological remodeling of arteries during hypertension in pregnancy. However, the mechanisms involved in this process remain unclear. We hypothesized that Neuropeptide Y (NPY), which is a potent mitogenic peptide, participates in modulating proliferation and migration of VSMCs during hypertension in pregnancy. Using pregnant hypertensive rats, induced by intraperitoneal injection of L-nitro-arginine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 45 publications
0
24
1
Order By: Relevance
“…These results are consistent with Grisé et al 12 who showed increased plasma NPY levels in control group compared to restraint group, while Hassan et al 13 showed same results in a study conducted on mice. Our results are not in agreement with Zhang et al 14 who showed decreased NPY levels in control group, the difference may be due to use of rodent female rat strain and use of different kits. Eskandarzade N et al 15 showed same plasma NPY level of control group and in starved rats.…”
Section: Discussioncontrasting
confidence: 99%
“…These results are consistent with Grisé et al 12 who showed increased plasma NPY levels in control group compared to restraint group, while Hassan et al 13 showed same results in a study conducted on mice. Our results are not in agreement with Zhang et al 14 who showed decreased NPY levels in control group, the difference may be due to use of rodent female rat strain and use of different kits. Eskandarzade N et al 15 showed same plasma NPY level of control group and in starved rats.…”
Section: Discussioncontrasting
confidence: 99%
“…The proliferation and migration of vascular smooth muscle cells plays a vital role in pathophysiological remodeling of arteries during hypertension in pregnancy. NPY could promote the proliferation and migration of vascular smooth muscle cells via Y1, Y5 receptors and in vascular tissues in vivo via Y5 receptor [128]. Human hypertension is heritable [129], and exhibits pleiotropic determination with autonomic activity.…”
Section: The Characteristics Of Human Npy Receptorsmentioning
confidence: 99%
“…The hypertrophic effect of NPY is accompanied by increased activity of cytosolic creatine kinase, protein kinase C, and protein kinase C-dependent activation of mitogen activated protein kinase in adult and neonatal myocytes and activation of phosphoinositol 3-kinase in adults (Protas et al 2003). Via its Y1R, Y2R, and Y5R, NPY promotes angiogenesis (Kuo et al 2007;Parker and Balasubramaniam 2008;Zhang et al 2015), where the Y5R acts as an enhancer (Movafagh et al 2006). In rats, the transmural number of capillaries in the left ventricle increases 3-fold from 1 to 5 days and 5-fold from 1 to 11 day of life.…”
Section: Discussionmentioning
confidence: 99%
“…Via its Y1R, Y2R, and Y5R, NPY promotes angiogenesis and preadipocyte differentiation (Kuo et al 2007;Parker and Balasubramaniam 2008;Zhang et al 2015). NPY has been shown to be a potent, multifunctional angiogenic factor, which stimulates proliferation, migration, and capillary tube formation in endothelial cells.…”
Section: Introductionmentioning
confidence: 99%